A rare ginsenoside compound K (CK) induces apoptosis for breast cancer cells - Seun Eui Kim; Myoung-Hoon Lee; Hye-Myoung Jang; Wan-Taek Im; Joontaik Lee; Sang-Hwan Kim; Gwang Joo Jeon (The Korean Society of Animal Reproduction and Biotechnology, 2023)
Background: A breast cancer is the second leading cause of cancer death in women worldwide and among different types of breast cancers, triple-negative breast cancer (TNBC) has a poor prognosis. Methods: We investigated the potential of ginsenoside compound K (CK), an active ingredient in the bio-transformed ginsenoside, to be used as a therapeutic ingredient by examining the effects of CK on cell proliferation, apoptosis, and cancer-related gene expressions in breast cancer cells. Results: From the results of treating MCF-7, an ER and PR-positive breast cancer cells, and MDA-MB-231 (TNBC) with CK at a concentration of 0-100 μM, the half maximal inhibitory concentration (IC50) values for each cell were 52.17 μM and 29.88 μM, respectively. And also, it was confirmed that cell migration was inhibited above the IC50 concentration. In addition, fluorescence analysis of Apoptosis/Necrosis showed that CK induced apoptosis rather than necrosis of breast cancer cells. Through qPCR, it was confirmed that the expression of genes related to apoptosis and cell cycle arrest was increased in CK-treated breast cancer cells, and it acted more effectively on TNBC. However, the expression of genes related to tumor invasion and metastasis is also increased, so it is necessary to consider the timing of application of CK as a potential therapeutic anticancer compound. Conclusions: CK showed a stronger inhibitory effect in TNBC with poor prognosis but considering the high tumor invasion and metastasis-related gene expression, the timing of application of CK should be considered.